"Hey Wait a Minute, Let's Look at the Data!" The Effects of Recording on Counselors and Clients - Gelso, Charles J.; Maryland Univ., College Park. Counseling Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
Early research on the effects of audio recording on counselors and clients found no adverse effects, particularly on clients. This research fostered a set of beliefs about recording which is now being extrapolated to the area of video observation. Recent research, however, does suggest that audio and, in particular, video recording has an inhibitory effect on clients and counselors. The nature of these effects on clients has been found to depend on several client characteristics. While recording is not as inhibitory as clients expect it to be, counselors tend not to be sensitive to the inhibiting effects that do occur in their clients. Implications of recent research for counselors are examined. (Author)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiotape Recordings; Client Characteristics (Human Services); Counseling; Counseling Effectiveness; Counseling Services; Counselor Characteristics; Inhibition; Tape Recordings